Efficient Modeling and Control of Large-Scale Systems - Mohammadpour, Javad; Grigoriadis, Karolos M.; SpringerLink (Online service) (Boston, MA : Springer US, 2010)
Complexity and dynamic order of controlled engineering systems is constantly increasing. Complex large scale systems (where "large" reflects the system$1 (Bs order and not necessarily its physical size) appear in many engineering fields, such as micro-electromechanics, manufacturing, aerospace, civil engineering and power engineering. Modeling of these systems often result in very high-order models imposing great challenges to the analysis, design and control problems. "Efficient Modeling and Control of Large-Scale Systems" compiles state-of-the-art contributions on recent analytical and computational methods for addressing model reduction, performance analysis and feedback control design for such systems. Also addressed at length are new theoretical developments, novel computational approaches and illustrative applications to various fields, along with: - An interdisciplinary focus emphasizing methods and approaches that can be commonly applied in various engineering fields -Examinations of applications in various fields including micro-electromechanical systems (MEMS), manufacturing processes, power networks, traffic control "Efficient Modeling and Control of Large-Scale Systems" is an ideal volume for engineers and researchers working in the fields of control and dynamic systems.s
Model Reduction, Large-Scale System Modeling and Applications -- Interpolatory Model Reduction of Large-Scale Dynamical Systems -- Efficient Model Reduction for the Control of Large-Scale Systems -- Dynamics of Tensegrity Systems -- Modeling a Complex Aero-Engine Using Reduced Order Models -- Large-Scale Systems Control and Applications -- Robust Control of Large-Scale Systems: Efficient Selection of Inputs and Outputs -- Decentralized Output-Feedback Control of Large-Scale Interconnected Systems via Dynamic High-Gain Scaling -- Decentralized Output Feedback Guaranteed Cost Control of Uncertain Markovian Jump Large-Scale Systems: Local Mode Dependent Control Approach -- Consensus Based Multi-Agent Control Algorithms -- Graph-Theoretic Methods for Networked Dynamic Systems: Heterogeneity and H2 Performance -- A Novel Coordination Strategy for Multi-Agent Control Using Overlapping Subnetworks with Application to Power Systems -- Distributed Control Methods for Structured Large-Scale Systems -- Integrated Design of Large-Scale Collocated Structural System and Control Parameters Using a Norm Upper Bound Approach.
Keywords: Engineering; Systems theory; Vibration; Control engineering systems; Engineering; Control , Robotics, Mechatronics; Vibration, Dynamical Systems, Control; Systems Theory, Control